ANALYSIS OF THE DECISION OF THE STATE ADMINISTRATIVE COURT IN DECISION NUMBER: 214/G/2022/PTUN.PLG ON THE DISPUTE OF KONI MANAGEMENT OF MUSI BANYUASIN REGENCY - Novia Febriani; Sri Suatmiati; Helwan Kasra (Universitas Labuhanbatu, 2024)
This research aims to analyze the analytical factors of the decision of the state administrative court in decision Number: 214/G/2022/PTUN.PLG regarding the dispute between Koni administrators of Musi Banyuasin district, and find out what the judge took into consideration regarding the decision letter of the general chairman of KONI of Sumatra Province South Number: 189 Year Number: 214/G/2022/PTUN.PLG. The method used in this research is descriptive normative legal research.Based on the results of the research, the panel of judges is of the opinion that the main issue in this case is the Plaintiff's demand to declare the object of the dispute null or invalid. Pay close attention to the object of the dispute which meets the elements of a state administration decision or government administration decision, because it is a written determination in the form of a decision made. issued by the defendant, namely KONI of South Sumatra Province, which contains state administrative legal action in the form of confirming the personnel composition of the protective board. The judge's basic consideration is that the a quo dispute is a sports dispute, where sports disputes are regulated in the Law on Sports. Keywords : Court Decision, Dispute, Koni Musi Banyuasin Regency